P21 Illness perceptions of neurologists and psychiatrists in relation to epilepsy and non-epileptic attack disorder (NEAD). Issue 10 (7th September 2012) - Whitehead, K; Reuber, M
Abstract : Objective: To contrast the illness perceptions of neurologists and psychiatrists towards NEAD with those towards epilepsy and to compare the illness perceptions, of the two professional groups, with each other and with those of patients. Method: Members of the BNPA and the UK Chapter of the International League Against Epilepsy were approached by email. 45 neurologists and 40 psychiatrists followed a Survey Monkey link to complete two versions of our adapted illness perception questionnaire-revised (IPQ-R) and our adapted symptom attribution question (SAQ), about epilepsy and NEAD. Data were analysed using Wilcoxon signed ranks and the Mann–Whitney U test, interpreting two-sided p values of 0.02 as significant. Results: Overall, psychiatrists seemed to have a less polarised view than neurologists of the "physical" nature of epilepsy on the one hand and the "psychological" nature of NEAD on the other. However, the majority of respondents clearly understood both epilepsy and NEAD as neuropsychiatric disorders. Like other healthcare workers surveyed previously, neurologists and psychiatrists professed a better understanding of epilepsy than of NEAD and thought that patients with NEAD had more control over their seizures than did those with epilepsy. The latter is at variance with patients' own experience. Unlike neurologists, psychiatrists thought of NEAD as a less chronic disorder than epilepsy. Conclusion: This study provides some interesting insights into neurologists', psychiatrists' and patients' understanding of epilepsy and NEAD. It demonstrates the potential for problems with communication and treatment, which might arise between patients and doctors and as patients are referred from one specialty to the other.